Biochemical and molecular characterization of Bacillus pumilus isolated from coastal environment in Cochin, India - Parvathi, Ammini (Sociedade Brasileira de Microbiologia, 2009)
Bacillus species constitute a diverse group of bacteria widely distributed in soil and the aquatic environment. In this study, Bacillus strains isolated from the coastal environment of Cochin, India were identified by detailed conventional biochemical methods, fatty acid methyl ester (FAME) analysis and partial 16S rDNA sequencing. Analysis of the data revealed that Bacillus pumilus was the most predominant species in the region under study followed by B. cereus and B. sphaericus. The B. pumilus isolates were further characterized by arbitrarily primed PCR (AP-PCR), antibiotic sensitivity profiling and PCR screening for known toxin genes associated with Bacillus spp. All B. pumilus isolates were biochemically identical, exhibited high protease and lipase activity and uniformly sensitive to antibiotics tested in this study. One strain of B. pumilus harboured cereulide synthetase gene cesB of B. cereus which was indistinguishable from rest of the isolates biochemically and by AP-PCR. This study reports, for the first time, the presence of the emetic toxin gene cesB in B. pumilus.